Donati resigns arts council (Raton, NM Raton Range, 1995)
Article is about Marilyn Donati resigning from the Art and Humanities Council.
Newspaper article + Photograph of Marilyn Donati.
Master list item #: 104
File location is in the Raton file Cabinet
Keywords: Donati, Marilyn -- Former Art and Humanities Council Director; Old Pass Gallery; Art and Humanities; Director Resignations; Raton, New Mexico